Optimal subwavelength design for efficient light trapping in central slit of plasmonics-based metal-semiconductor-metal photodetector - Masouleh, F.; Das, Narottam; Rozati, S. (Springer New York LLC, 2015)
© 2015, Springer Science+Business Media New York. We present the analysis of a novel plasmonics-based metal-semiconductor-metal photodetector that dramatically modifies the light transmission spectra when the sub-wavelength central slit is partly covered with a gold (Au) thin film. The simulation results reveal surface plasmons together with the optimized nano-gratings impact in this special design for quality light absorption inside the device active region. Finite-difference time-domain method has been utilized to simulate the behavior of the proposed novel photodetector structure with significant improved light absorption capacity.